2010
DOI: 10.1002/ctpp.201010144
|View full text |Cite
|
Sign up to set email alerts
|

Towards Fast Measurement of the Electron Temperature in the SOL of ASDEX Upgrade Using Swept Langmuir Probes

Abstract: On ASDEX Upgrade first experiments were made using single probes with a voltage sweep frequency up to 100kHz. Possibilities and limitations using fast swept probes with a standard diagnostic and analysis tools are discussed. A good agreement between the data derived from fast swept single probe characteristics and floating as well as saturation current measurements was found. In a stationary (non ELMing) plasma the data of the fast swept probe are compared to standard slow swept probes (kHz range) showing an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Figure 11 shows n e , T e , V flt , and I ratio determined from the fast swept single probe (black data) during an ELM which starts at significantly lowered compared to the pedestal top temperature of about 600 eV. Starting at 3.9805s there is a good correlation of the n e,fl and T e,fl peaks as shown in figure 11 (see also [20] Investigations on T i in ELM filaments indicated that T i > T e . In [34].…”
Section: Elm Filament Temperaturesmentioning
confidence: 73%
See 2 more Smart Citations
“…Figure 11 shows n e , T e , V flt , and I ratio determined from the fast swept single probe (black data) during an ELM which starts at significantly lowered compared to the pedestal top temperature of about 600 eV. Starting at 3.9805s there is a good correlation of the n e,fl and T e,fl peaks as shown in figure 11 (see also [20] Investigations on T i in ELM filaments indicated that T i > T e . In [34].…”
Section: Elm Filament Temperaturesmentioning
confidence: 73%
“…To measure ion energies, a retarding field analyzer (RFA) [19] was operated in ELMy H-mode. For investigations where high heat loads have to be expected a Mach type probe head with ten in-plane Langmuir probes (HHF) [20] similar to flush mounted probes was exposed to the plasma. Five pins were poloidally staggered at each side of the probe.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…eV [17,18]. However, it should be noticed that none of these scarce e T measurements are available for the discharge parameters discussed here.)…”
Section: Retarding Field Analyzermentioning
confidence: 94%
“…The BPP screens the electrons by magnetic field in order to achieve α ≈ 0, because ions with larger Larmor radius can penetrate inside the hole, whilst the electrons cannot. Detailed comparison with other diagnostics demonstrated such functionality [5,3] Especially, direct comparison with 100kHz-swept Langmuir probe LP 3 shows quite good agreement [7] in absolute values up to high frequencies. It was found experimentally [3] that α bpp = 0.6 ± 0.3.…”
Section: Introductionmentioning
confidence: 99%